A pivotal role of phosphatidylinositol 3-kinase in delaying of methyl jasmonate-induced leaf senescence. (2nd June 2016) - Liu, Jian; Zhou, Jun; Xing, Da
ABSTRACT: Phosphatidylinositol 3-kinase (PI3K) and its product PI3P are involved in plant development and stress responses. Our recent report has suggested that down-regulation of PI3K activity accelerated leaf senescence induced by methyl jasmonate (MeJA) and suppressed the activation of vacuolar H + -ATPase (V-ATPase). In vitro and in vivo experiment revealed that PI3K interact with VHA-B2. The inhibition of V-ATPase activity suppressed the vacuolar acidification and enhanced the stomatal opening, thereby accelerating MeJA-induced leaf senescence. It was shown that there is close relationship between PI3K and V-ATPase. However, the factor which initiates the PI3K-V-ATPase pathway needs further improvement, and the domain of VHA-B that binds to PI3K is still not clear enough. By using the Arabidopsis and MeJA as the research model, studies have been performed to investigate the upstream regulation of PI3K and downstream function of PI3K-V-ATPase pathway in the plant senescence.